Pelatihan Penyusunan Surat Melalui Mail Merge Bagi Perangkat Gampong Kecamatan Peureulak - Jamali; Rizki, Muhammad; Zuboili (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This training aims to provide knowledge and skills to gampong officials in Peureulak District in using the mail merge technique to compose letters efficiently and effectively. Participants will learn the steps in creating a template document that includes design patterns, formats, and variable settings that will be used to combine data. Next, participants will learn how to integrate data from external sources such as Excel into Word documents using the mail merge feature. They will learn how to set data filtering criteria, edit and modify documents, and add dynamic elements such as tables, images, and graphs. Training will also cover common troubleshooting techniques related to mail merge, such as resolving data merge errors, fixing incorrect formatting, and optimizing processes to increase productivity. Participants will be involved in hands-on practical sessions where they will be given the opportunity to try out the techniques, they have learned for themselves. This will help them hone their skills and gain confidence in using mail merge in their daily work. This training can provide significant benefits for gampong officials in Peureulak District, enabling them to improve efficiency and accuracy in compiling letters. By using mail merge, the process of writing letters can be automated, saving time and reducing the risk of human error.